2012
DOI: 10.3109/0284186x.2011.652738
|View full text |Cite
|
Sign up to set email alerts
|

Long-term local control achieved after hypofractionated stereotactic body radiotherapy for adrenal gland metastases: A retrospective analysis of 34 patients

Abstract: (2012) Long-term local control achieved after hypofractionated stereotactic body radiotherapy for adrenal gland metastases: A retrospective analysis of 34 patients, Acta Oncologica, 51:5, 618-623,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 19 publications
6
47
1
4
Order By: Relevance
“…It should be noted that in the four studies which showed a lower rate of local control, the median biologically equivalent dose delivered was lower than 60 Gy. 21,22,25,26 In contrast, studies delivering higher biologically equivalent doses (BED median > 85 Gy, BED maximum value 132-137 Gy, ˛/ˇ = 10) 20,27,28 reported a 2-year local control ≥ 90%. These data are consistent with that indicating that a BED greater or equal to 100 Gy is necessary to control primary NSCLC.…”
Section: Efficacymentioning
confidence: 99%
“…It should be noted that in the four studies which showed a lower rate of local control, the median biologically equivalent dose delivered was lower than 60 Gy. 21,22,25,26 In contrast, studies delivering higher biologically equivalent doses (BED median > 85 Gy, BED maximum value 132-137 Gy, ˛/ˇ = 10) 20,27,28 reported a 2-year local control ≥ 90%. These data are consistent with that indicating that a BED greater or equal to 100 Gy is necessary to control primary NSCLC.…”
Section: Efficacymentioning
confidence: 99%
“…Historically, surgical excision provided better outcome in terms of median survival and overall survival than other local treatments. The advent of SABR led to promising clinical results in this setting in terms of local control, even though most of the case series have a slender sample size and short follow-up time, as summarized in TABLE 2 [34][35][36][37][38]. In a series of homogeneously treated patients from Florence University [37], in the majority the prescription dose was 36 Gy in three fractions, with eight patients treated with a single-fraction.…”
Section: Adrenal Metastasesmentioning
confidence: 96%
“…Imaging should ideally have been performed within 2 months of therapy. 38 Biopsy of an adrenal mass in this setting remains controversial. It has been proposed as mandatory by some, 20,21,24,50,53 especially in a patient with potentially curable intrathoracic disease.…”
Section: Work-up and Patient Selectionmentioning
confidence: 99%
“…Patients in three of the studies received systemic therapy before, after, or concurrent with RT (Table 5). However, cytotoxic systemic therapy was commonly held for 2-4 weeks 23,38 before SBRT and restarted up to 8 weeks after its completion. 38 …”
Section: Radiation Therapymentioning
confidence: 99%
See 1 more Smart Citation